Genetic dissection of zinc, iron, copper, manganese and phosphorus in wheat (Triticum aestivum L.) grain and rachis at two developmental stages - Cu, Suong T.; Guild, Georgia E.; Nicolson, Alison; Velu, Govindan; Singh, Ravi P.; Stangoulis, James (Elsevier, 2020)
The development of high-yielding wheat genotypes containing micronutrient-dense grains are the main priorities of biofortification programs. At the International Maize and Wheat Improvement Center, breeders have successfully crossed high zinc progenitors including synthetic hexaploid wheat, T. dicoccum, T. spelta and landraces to generate high-zinc varieties. In this study, we report a genome-wide association using a wheat diversity panel to dissect the genetics controlling zinc, iron, copper, manganese and phosphorus concentrations in the grain and rachis during grain development and at physiological maturity. Significant marker-trait associations (MTAs) were identified for each nutrient using multi-locus mixed model methodologies. For mature grain, markers that showed significant pleiotropic effects were found on chromosomes 1A, 3B and 5B, of which those on chromosome 5B at ∼95.5 cM were consistent over two growing seasons. Co-located MTAs were identified for the nutrient concentrations in developing grain, rachis and mature grain on multiple chromosomes. The identified genomic regions included putative candidate genes involved in metal uptake and transport and storage protein processing. These findings add to our understanding of the genetics of the five important nutrients in wheat grain and provide information on genetic markers for selecting high micronutrient genotypes.